Effect of crop density on yield of bean Pinto Saltillo under irrigation in Chihuahua, Mexico - Jiménez Galindo José Cruz; Acosta Gallegos, Jorge Alberto (Revista Mexicana de Ciencias Agrícolas, 2018)
There are studies describing the use of the high densities in bean under irrigation in the state of Chihuahua. Most irrigation bean producers harvest a density below the recommendations from INIFAP. The objectives of the studies reported here were: a) to perform a random sampling in commercial plots of bean producers under irrigation in Chihuahua to determine the population of plants in use, and b) evaluate the grain yield of the variety Pinto Saltillo under irrigation with different densities, locations and years. The sampling density in plots of irrigated bean producers was conducted in 2009. Experiments to determine the use of high density or optimum densities were performed in 2010 in Francisco I. Madero, Bachiniva and in 2011 in Carbajal de Abajo, Cusihuiriachi and Independence, Namiquipa. At each location was used the irrigation system available for the producer, center pivot irrigation in the first two locations and at the third location hand move sprinkler irrigation system. Fertilization and management varied according to the producer. The densities used varied from 1 to 16 plants per meter (plant per m-1). The average density recommended for beans under irrigation in the three locations was 8 plant m-1 (100 000 plants per hectare at harvest). In determining an average of grain yield in the three areas studied, result an increase of 1 966.2 to 2 305.7 kg ha-1, thus optimum planting density could be increased bean yield under irrigation as the Federal Government anticipates increasing the national average of bean under irrigation from 1 700 kg ha-1 to a range of 2 000 to 2 500 kg ha-1.